Uphill running capacity in Swiss elite orienteers - Zürcher, S.; Clenin, G.; Marti, B. (BASPO, 2007)
The purpose of this study was to quantify uphill running capacity in a laboratory treadmill test with Swiss elite and junior orienteers, and to evaluate the differences between flat and uphill running capacity.